2021
DOI: 10.1007/s11266-020-00306-6
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Players? The Third Sector and Employability Services for Migrants, Refugees and Asylum Seekers in the UK

Abstract: Literature in the field of employability and the third sector has focused upon the impact of marketisation on third sector providers, elaborating how commissioning processes have led to a contraction of (smaller) third sector organisations (TSOs) and an expansion of larger private sector bodies. Extant research does not however explore the role of third sector organisations in the employability of migrants, refugees and asylum seekers. Therefore, our paper explores this gap by adopting a qualitative approach v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…The rising numbers of refugees in both countries prompted various policy responses at the state level, for example, Brazil granting Venezuelans the right to work and settle under a humanitarian reception scheme and the UK launching the Syrian Vulnerable Persons Resettlement Scheme (SVPRS) (Mavelli, 2017;Mayblin & James, 2019;Morano-Foadi et al, 2021;Moreira, 2014;Moreira & Baeninger, 2010). However, studies have shown that in both contexts, service provision was provided by a disparate range of actors, with variable levels of coordination and discontinuous funding available to service providers (see Calò et al, 2021;Morano-Foadi et al, 2021 for the UK, and Baeza, 2018;Ianni Segatto, 2021;Moreira, 2017 for Brazil).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rising numbers of refugees in both countries prompted various policy responses at the state level, for example, Brazil granting Venezuelans the right to work and settle under a humanitarian reception scheme and the UK launching the Syrian Vulnerable Persons Resettlement Scheme (SVPRS) (Mavelli, 2017;Mayblin & James, 2019;Morano-Foadi et al, 2021;Moreira, 2014;Moreira & Baeninger, 2010). However, studies have shown that in both contexts, service provision was provided by a disparate range of actors, with variable levels of coordination and discontinuous funding available to service providers (see Calò et al, 2021;Morano-Foadi et al, 2021 for the UK, and Baeza, 2018;Ianni Segatto, 2021;Moreira, 2017 for Brazil).…”
Section: Resultsmentioning
confidence: 99%
“…A disparate range of organisations and their constituent actors influence migrants' transition into and through the labour market (Calò et al, 2021;Grosskopf et al, 2021;Siviş, 2021). Various informal networks, formal organisations and institutions including charities, branches of faith-based bodies, social enterprises and non-governmental organisations (NGOs) help to develop migrants' general employability and facilitate their access to work (Aerne & Bonoli, 2021;Bagavos & Kourachanis, 2021;İçduygu & Diker, 2017;Siviş, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another category includes the UK, where, as argued by Calo `et al, (2021) in this special issue, civil society often intervenes in the policy implementation of labour market services as a result of a neoliberal process of public retrenchment that began in the Thatcher era and was then never properly redressed by the following administrations. In the field of migration and integration in the labour market, the services delivered by third-sector organisations are limited due to the scarcity of funding and recent years' public budget cuts.…”
Section: Towards a Typology Of Civil Society Activation On Migrant La...mentioning
confidence: 99%
“…In regards to the UK, meanwhile, Calo `et al (2021) show that austerity measures have particularly affected CSOs working in the migration field, leading to a reduction of services (and specifically those in the field of employability) at a time of increasing migration and therefore increasing needs. The paper argues that CSOs are collaborators of public authorities in integration services, aiming to improve the system without taking any political stance, thereby becoming more partners in the design of policy and new services than proper vectors of policy change.…”
Section: The Special Issue Papersmentioning
confidence: 99%